Perception of earbuds side effects among teenager and adults in Eastern Province of Saudi Arabia: A cross sectional study - Abdullah A. Alarfaj; Lujain M. AlAhmmed; Sayed Ibrahim Ali (Elsevier, 2021)
Background: As technology keeps on developing, earbuds have been more popular recently among different age groups. As they are inserted into the external ear canal, they obstruct and isolate its communication with the outer environment. Thus, changing temperature and humidity inside the external ear canal. (EEC), and the extent of those environmental changes is influenced by the duration of using the earbuds, as well as, the attitude of maintaining hygiene of the earpieces. Material and methods: A cross sectional study was conducted among the teenager and adult population of AlAhssa, Dammam, AlQatif, and Jubail Industrial cities, Eastern Province, Saudi Arabia. An online validated voluntary self-administered questionnaire was disseminated. The questionnaire consisted of 19 elements including consent. The net data of 504 participants was analyzed with SPSS version 21. Results: Regular use of earbuds was found among 32.5% of the respondents. The mean knowledge score was 2.49 (SD 0.95) out of 4 points. Good, moderate and poor awareness were found among 49.2%, 35.3% and 15.5% respectively. The most commonly known symptoms of prolonged use of earbuds were itching (28%), otalgia (23%) and excessive ear wax (21.8%). It was found that females (T = −2.569; P = 0.010) and earbuds users for 1-2 h per day (F = 2.901; P = 0.040) have significantly better awareness while students (F = 2.824; P = 0.044) and those using high volume level have significantly poorer level of awareness. Conclusion: There was an adequate awareness toward the side effects of excessive usage of earbuds among teenagers and young adults. Females showed better awareness compared to males and short-term usage of earbuds was a significant predictor of good awareness.